Time-resolved, defect-hosted, trace element mobility in deformed Witwatersrand pyrite - Fougerouse, Denis; Reddy, Steven; Kirkland, Chris; Saxey, David; Rickard, William; Hough, R. (Elsevier, 2018)
© 2018 China University of Geosciences (Beijing) and Peking University The Pb isotopic composition of rocks is widely used to constrain the sources and mobility of melts and hydrothermal fluids in the Earth's crust. In many cases, the Pb isotopic composition appears to represent mixing of multiple Pb reservoirs. However, the nature, scale and mechanisms responsible for isotopic mixing are not well known. Additionally, the trace element composition of sulphide minerals are routinely used in ore deposit research, mineral exploration and environmental studies, though little is known about element mobility in sulphides during metamorphism and deformation. To investigate the mechanisms of trace element mobility in a deformed Witwatersrand pyrite (FeS2), we have combined electron backscatter diffraction (EBSD) and atom probe microscopy (APM). The results indicate that the pyrite microstructural features record widely different Pb isotopic compositions, covering the entire range of previously published sulphide Pb compositions from the Witwatersrand basin. We show that entangled dislocations record enhanced Pb, Sb, Ni, Tl and Cu composition likely due to entrapment and short-circuit diffusion in dislocation cores. These dislocations preserve the Pb isotopic composition of the pyrite at the time of growth (~3 Ga) and show that dislocation intersections, likely to be common in deforming minerals, limit trace element mobility. In contrast, Pb, As, Ni, Co, Sb and Bi decorate a high-angle grain boundary which formed soon after crystallisation by sub-grain rotation recrystallization. Pb isotopic composition within this boundary indicates the addition of externally-derived Pb and trace elements during greenschist metamorphism at ~2 Ga. Our results show that discrete Pb reservoirs are nanometric in scale, and illustrate that grain boundaries may remain open systems for trace element mobility over 1 billion years after their formation.